Trend Inflation, Taylor Principle and Indeterminacy - Guido Ascari; Tiziano Ropele (Kiel Institute for the World Economy (IfW), 2007)
We show that low trend inflation strongly aects the dynamics of a standard Neo-Keynesian model where monetary policy is described by a standard Taylor rule. Moreover, trend inflation enlarges the indeterminacy region in the parameter space, substantially altering the so-called Taylor principle. The main results hold for dierent types of Taylor rules, inertial policy rules and indexation schemes. The key message is that, whatever the set up, the literature on Taylor rules cannot disregard average inflation in both theoretical and empirical analysis.
Keywords: E52; E31; 330; Sticky Prices; Taylor Rules and Trend Inflation; Preisrigidität; Inflation; Taylor-Regel; New-Keynesian Phillips Curve; Theorie